Seasonal variation in gas exchange and chlorophyll index of Palicourea racemosa in an open ombrophilous forest - dosSantos Coêlho, Ester; da Silva Ribeiro, João Everthon; Andrade Figueiredo, Francisco Romário; Pereira Leite, Arliston; Ferreira Melo, Marlenildo; Bandeira de Albuquerque, Manoel (BOSQUE, 2021)
Seasonal variation affects understory and canopy tree plants in different ways. Palicourea racemosa is an understory shrub from the Rubiaceae family and is subject to seasonal oscillations of the environment, which can affect plant ecophysiological responses. This species is widely distributed in humid forests from southern Mexico to southeastern Brazil and has broad economic and ecological importance for the regions of occurrence, being used for food, ornamental and traditional medicine purposes. It is of fundamental importance to know ecophysiological responses of this species throughout dry and rainy periods, to understand the dynamics of understory plants in tropical forests. This research aimed at evaluating the effects of seasonality on ecophysiological aspects of P. racemosa at the Mata do Pau-Ferro State Park, municipality of Areia, Paraíba, Brazil. Over ten months, upper canopy structure indices were measured in ten individuals, climatic data were collected and their effects on gas exchange and chlorophyll indices in plants were evaluated. Results showed that the environmental variables correlated with the ecophysiological ones, with a strong association of soil moisture, rainfall and leaf area index of the upper canopy on ecophysiological aspects in P. racemosa plants, indicating that water availability and irradiance affect gas exchanges and photosynthetic pigment content. Except for intrinsic water use efficiency and instantaneous carboxylation efficiency, all ecophysiological variables showed significant differences over the months, showing the influence of seasonality on the ecophysiological responses of P. racemosa.